205k views
18 votes
Evaluate the following expressions for x = 2.

–9.2(4 – x)
–9.2(4 – (2))
–9.2(2)


Evaluate the following expression for x = 2.
-36.8 + 9.2x

2 Answers

4 votes

Answer:

-18.4 and -18.4

Step-by-step explanation:

hope this helped :)

User Ahamed Mustafa M
by
6.3k points
10 votes

Answer:


-9.2(4 - x) = -18.4


-36.8 + 9.2x =-18.4

Step-by-step explanation:

Given


-9.2(4 - x)


-36.8 + 9.2x

Required

Evaluate when
x =2


-9.2(4 - x)

Substitute 2 for x


-9.2(4 - x) = -9.2(4 - 2)

Evaluate the expression in bracket


-9.2(4 - x) = -9.2(2)

Remove bracket


-9.2(4 - x) = -9.2*2


-9.2(4 - x) = -18.4


-36.8 + 9.2x

Substitute 2 for x


-36.8 + 9.2x = -36.8 + 9.2 * 2


-36.8 + 9.2x = -36.8 + 18.4


-36.8 + 9.2x =-18.4

User Vianey
by
6.1k points